An Unusual Complication of Intralesional Corticosteroid Injections: Two Case Reports - Khadiri, Omayma; Kaoua, Rim; Aboudourib, Maryem; Amal, Said; Hocar, Ouafa (Current Rheumatology Reviews, 2025)
<span class=
Keywords: Intralesional corticosteroid injections; tenosynovitis; wood’s lamp examination; synovial cyst; hypopigmentation; musculoskeletal conditions